2017
DOI: 10.3892/mmr.2017.7464
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of curcumin alleviate lumbar intervertebral disc degeneration through regulating the expression of iNOS, COX-2, TGF-β1/2, MMP-9 and BDNF in a rat model

Abstract: Curcumin is a natural product with antimutagenic, antitumor, antioxidant and neuroprotective properties. However, to the best of our knowledge, curcumin has yet to be investigated for the treatment of lumbar intervertebral disc degeneration LIDD). The aim of the present study was to investigate whether curcumin can alleviate LIDD through regulating the expression of inducible nitric oxide synthase (iNOS), cyclooxygenase (COX)‑2, transforming growth factor (TGF)‑β1/2, matrix metalloproteinase (MMP)‑9 and brain‑… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In spine instability mouse models, Bian Q et al 10,103 observed that aberrant mechanical loading could lead to the excessive activation of TGF-b signaling and IVD degeneration, and administration of TbRI (ALK5) inhibitor suppressed the R-SMAD signaling and attenuated the IVD degeneration. And in a rabbit annular puncture model, Hu Y et al 105 found that halofuginone could delay the IVD degeneration and the inactivation of TGF-b signaling might be involved. Furthermore, the study of Kwon YJ et al 106 suggested that TGF-b1 was increased and could activate both SMAD2/3 and SMAD1/5/8 pathways in bovine NPCs under degenerative condition, and the activated SMAD1/5/8 pathway could negatively regulate the SMAD2/3 signaling, which resulted in further IVD degeneration.…”
Section: Excessive Activation Of Tgf-b Signaling May Contribute To IVmentioning
confidence: 99%
“…In spine instability mouse models, Bian Q et al 10,103 observed that aberrant mechanical loading could lead to the excessive activation of TGF-b signaling and IVD degeneration, and administration of TbRI (ALK5) inhibitor suppressed the R-SMAD signaling and attenuated the IVD degeneration. And in a rabbit annular puncture model, Hu Y et al 105 found that halofuginone could delay the IVD degeneration and the inactivation of TGF-b signaling might be involved. Furthermore, the study of Kwon YJ et al 106 suggested that TGF-b1 was increased and could activate both SMAD2/3 and SMAD1/5/8 pathways in bovine NPCs under degenerative condition, and the activated SMAD1/5/8 pathway could negatively regulate the SMAD2/3 signaling, which resulted in further IVD degeneration.…”
Section: Excessive Activation Of Tgf-b Signaling May Contribute To IVmentioning
confidence: 99%
“…In respect to its high incidence rate, finding treatments for LIDD is of importance. Increasing evidence demonstrates that TGF-β has dual role in different disorders, so that it may reduce the number of cells undergoing apoptosis in a certain circumstance, while it may enhance apoptotic cell death (Hu et al, 2017). Curcumin administration alleviates LIDD by inhibition of TGF-β1 and TGF-β2 signaling pathways.…”
Section: Neurological Disordersmentioning
confidence: 99%
“…Some studies suggested that the reduction of TGF-β1 leading decline of anabolic synthesis was the main cause of disc degeneration [ 1 , 3 , 26 ]. However, recent studies have shown that the expression of TGF-β1 in degenerative disc tissues was significantly increased [ 8 , 24 ], local excessively high concentration of TGF-β might accelerate the disc degeneration [ 15 , 29 ]. Additionally, abnormal expression of TGF-β might also lead to the decrease of type II collagen and the increase of type I collagen [ 4 , 17 ].…”
Section: Discussionmentioning
confidence: 99%